Giving Due Recognition: The Importance of Legislation To Improve the Status of Domestic Workers - Fadli Padila Putra; Riska Rahmawati (CV. Ulil Albab Corp, 2023)
This article aims to explain the importance of domestic workers laws to protect domestic workers' rights and provide proper recognition for domestic workers. This research is classified as literature research using related scientific journals as a reference source. The results of the study found that domestic workers were not substantively regulated by the Manpower Act No. 13 of 2003 because the status is different from other workers. With the data that has been provided regarding the many cases of violence, sexual harassment, the rights of domestic workers who have not been fulfilled are strong reasons for the formulation of the Law on Domestic Workers, and this is an important matter and must be acted upon.